The baby boom and World War II a macroeconomic analysis - Doepke, Matthias; Hazan, Moshe; Maoz, Yishay (Working paper series / National Bureau of Economic Research, 2007)
We argue that one major cause of the U.S. postwar baby boom was the increased demand for female labor during World War II. We develop a quantitative dynamic general equilibrium model with endogenous fertility and female labor-force participation decisions. We use the model to assess the long-term implications of a one-time demand shock for female labor, such as the one experienced by American women during wartime mobilization. For the war generation, the shock leads to a persistent increase in female labor supply due to the accumulation of work experience. In contrast, younger women who turn adult after the war face increased labor-market competition, which impels them to exit the labor market and start having children earlier. In our calibrated model, this general-equilibrium effect generates a substantial baby boom followed by a baby bust, as well as patterns for age-specific labor-force participation and fertility rates that are consistent with U.S data.